2008
DOI: 10.1007/s10620-008-0361-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action of Selenium-Enriched Probiotics Against Pathogenic Escherichia coli

Abstract: The purpose of this study was to evaluate the inhibitory activity of selenium-enriched probiotics against pathogenic Escherichia coli (E. coli) in vitro and in vivo. Escherichia coli was co-cultured in vitro with each probiotic strain individually, and a mixture of the four strains and its population was counted at various time points. We also collected a cell-free culture supernatant (CFCS) of each probiotic strain and the four-strain mix to examine their antibacterial activity, using the cylinder plate metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 40 publications
(42 reference statements)
4
63
0
2
Order By: Relevance
“…8 It was shown in that study that seleniumenriched probiotics (at a concentration of 0.509 µg selenium per gram of probiotics) inhibited the growth of E. coli after 96 hours in vitro. In vivo, mice were fed with and without selenium-enriched probiotics for 28 days and then inoculated with E. coli; mortality of the treated group was the lowest.…”
Section: Introductionmentioning
confidence: 96%
“…8 It was shown in that study that seleniumenriched probiotics (at a concentration of 0.509 µg selenium per gram of probiotics) inhibited the growth of E. coli after 96 hours in vitro. In vivo, mice were fed with and without selenium-enriched probiotics for 28 days and then inoculated with E. coli; mortality of the treated group was the lowest.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have suggested that organic Se is usually less toxic and more bioavailable than inorganic Se (Brown et al, 2000). Recently, research showed that some microorganisms were capable of accumulating large amounts of Se and transforming inorganic Se into organic Se (Suhajda et al, 2000;Yang et al, 2009;Jin et al, 2012). Of these microorganisms, Se-enriched yeast has been studied extensively and is now commercially available as a nutritional Se supplement (Suhajda et al, 2000).…”
Section: Preparation Of Selenium-enriched Bifidobacterium Longum and mentioning
confidence: 99%
“…Of these microorganisms, Se-enriched yeast has been studied extensively and is now commercially available as a nutritional Se supplement (Suhajda et al, 2000). In addition, Lactobacillus was also found to have the ability to transform inorganic Se into organic compounds (Yang et al, 2009). In our previous study, Se was enriched to transformed B. longum carrying pBV22210-endostatin (B. longum-En).…”
Section: Preparation Of Selenium-enriched Bifidobacterium Longum and mentioning
confidence: 99%
“…For example, selenium-enriched probiotics have been shown to strongly inhibit the growth of pathogenic Escherichia coli in vivo and in vitro. 9 The synthesized organoselenium compounds were shown to be as effective as penicillin at inhibiting Staphylococcus aureus growth in solution in vitro. 10 In addition, the growth of planktonic S. aureus was strongly inhibited in the presence of selenium nanoparticles.…”
Section: Introductionmentioning
confidence: 99%